2021
DOI: 10.24875/acm.20000088
|View full text |Cite
|
Sign up to set email alerts
|

Correlación del volumen de entrenamiento en MET-min/semana con el porcentaje de ganancia de VO2p-carga en pacientes con insuficiencia cardiaca con fracción de expulsión reducida, sometidos a un programa de rehabilitación cardiaca

Abstract: Resumen Objetivo: La insuficiencia cardiaca (IC) es un síndrome clínico caracterizado por disminución en la capacidad funcional. Los programas de rehabilitación cardiaca y prevención secundaria (PRHCyPS) han mostrado mejorar la calidad de vida y tolerancia al esfuerzo en este grupo de pacientes, pero sus efectos son dependientes del volumen. Nuestro objetivo es evaluar el grado de correlación del volumen de entrenamiento medido en equivalentes metabólicos (MET)-min/semana con el porce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
0
0
1
Order By: Relevance
“…Moreover, in their quasi-experimental study evaluating VO 2 p measured by exercise load, tested before and after a receiving a concurrent supervised conventional effort training program, Ku-González et al 5 determined that 70.6% were males, with an average age of 61.5 ± 8.9 years, and an average left ventricular ejection fraction of 38 ± 4.6%; 96.8% of the HF was ischemic, and 55.9, 29.4 and 5.9% were in New York Heart Association class I, II and III, respectively, with an average volume of 504.34 ± 164 MET-min/week. An analysis of the patients in the risk groups according to maximal effort tolerance through the VO 2 p reached on the initial stress test showed that they achieved a VO 2 pload of 5.9 ± 2.1 MET, and 74.4% of the population was in groups C and D, who achieved < 7 MET on the initial stress test.…”
Section: Capacidad Física Y Variables Fisiológicas Con Insuficiencia ...mentioning
confidence: 99%
“…Moreover, in their quasi-experimental study evaluating VO 2 p measured by exercise load, tested before and after a receiving a concurrent supervised conventional effort training program, Ku-González et al 5 determined that 70.6% were males, with an average age of 61.5 ± 8.9 years, and an average left ventricular ejection fraction of 38 ± 4.6%; 96.8% of the HF was ischemic, and 55.9, 29.4 and 5.9% were in New York Heart Association class I, II and III, respectively, with an average volume of 504.34 ± 164 MET-min/week. An analysis of the patients in the risk groups according to maximal effort tolerance through the VO 2 p reached on the initial stress test showed that they achieved a VO 2 pload of 5.9 ± 2.1 MET, and 74.4% of the population was in groups C and D, who achieved < 7 MET on the initial stress test.…”
Section: Capacidad Física Y Variables Fisiológicas Con Insuficiencia ...mentioning
confidence: 99%
“…En el 2020, en la Universidad del Gran Rosario 3 , se realizó una revisión bibliográfica, de tipo retrospectivo y cualitativo, a partir de diez artículos seleccionados mediante búsqueda en las bases de datos científicas. Entre diferentes estudios analizados se menciona un estudio por Rhodes et al 4 , en el que se observa que, durante los seis meses previos al inicio del programa de rehabilitación, 188 pacientes de 6 a 17 años completaron pruebas de ejercicio con análisis de gases espiratorios, 71 de los cuales no tenían un defecto cardíaco congénito de gravedad suficiente para ser incluido en el estudio, y 33 fueron excluidos porque tenían un VO 2máx y tasa de trabajo pico inferior al 80% predicho. Se encontró que, bajo efecto del programa de rehabilitación cardíaca en el ejercicio pico, hubo un aumento significativo en el VO 2máx (de 26.4 ± 9.1 a 30.7 ± 9.2 ml/kg/min) y la tasa de trabajo pico (de 93 ± 32 a 106 ± 34 W).…”
unclassified